Worship and the Lord"s Supper in Assemblies of God, and other selected Pentecostal churches in Nigeria - Mbamalu, Williams O. (HTS teologiese studies, 2015)
Pentecostals’ dominant liturgical principle has traditionally taken the pattern of unlimited expression of emotion and charismata, often formless and emphasising the subjective. The manifestations of the Spirit’s direct activity often interpreted as the reason for Pentecostals’ antiliturgical position, have in the past few years passed through a paradigm shift. The introduction of concrete rituals encompassing various significations, in a manner reminiscent of African traditions and culture by some churches, shows uncritical engagement with biblical theology of worship. Furthermore, the encouragement of individual appropriation of God’s promise in rites performance is a deviation from African traditional emphasis on community function. The researcher employed a participant observation methodology and engagement with pertinent literary works of pastors of the churches investigated. The article shows that the struggle of Pentecostals to be relevant is responsible for its juxtaposition of African traditions and culture with the Spirit in the performance of liturgical rites. The article concludes that in Nigeria Pentecostals’ practice of worship encourages the individual to appropriate the biblical promises of God at the expense of the community of Christ whose work in building character and guiding our lives is done through other Christians in the community.